Education of clean and healthy living behavior through image media as a prevention of Covid-19 - Kriswanto, Erwin Setyo; Sunardi, Jaka; Sari, Indah Prasetyawati Tri Purnama; Suharjana, Fredericus (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2020)
The purpose of this community service activity is to optimize the behavior of a clean and healthy life through media images as an effort to prevent Covid-19 in Tlogo Prambanan Village, Klaten. The method used in this service activity is to socialize clean and healthy living habits during the Covid-19 outbreak through media images. Another method is to provide booklets to the public regarding Covid-19 prevention procedures and provide direction to teams or field officers regarding disinfectant spraying protocols. The results of the activity of dedicating a clean and healthy lifestyle through image media in the village of Tlogo, Prambanan Klaten, run optimally. The community stated that the media images provided during the activity were very useful and communicative, making it easier for people to learn about clean and healthy living habits as part of efforts to prevent and break the chain of transmission of Covid 19 in the community. Of the target targets who filled Google Form as many as 181 people, there was a 95% change in behavior due to image media.